A conceptual model for the shakedown response of soft clay to high-cycle, low-amplitude undrained loading. (April 2023) - Zhao, Chuang; Liu, Jiaming; Liu, Hongming; Bian, Xuecheng; Chen, Yunmin
Abstract: Soft soils beneath transportation infrastructures suffer dynamic traffic loads with high-frequency and high-cycle characteristics, which mainly present shakedown development of deformation yet probably induce notable deformation at the stable state. However, conventional constitutive models are still not available for the long-term behavior description of soft soils under high-cycle traffic loading. Herein, a conceptual model for high-cycle, low-amplitude undrained loading was proposed incorporating a shrinking yield surface and an expanding boundary surface, which individually indicated the weakening behavior caused by an increase in excess pore water pressure and the hardening effect due to contractive plastic deformation. Given the shakedown responses of soft soils, a mapping ratio and a one-time calculation approach were employed. Thus, the effect of loading frequency on the response of soft soil can be considered, and the calculation efficiency was greatly improved. Then, the evaluation of model parameters and parametric analyses on the loading frequency, shrinking yield surface, expanding boundary surface and mapping ratio were carried out to examine the performance of the proposed model. To further validate the proposed model, undrained cyclic triaxial tests on reconstituted Ningbo clay were conducted, and high-cycle undrained triaxial tests on Kaolin clay and Ariake clay were referenced. The predicted developments of accumulated plastic deviatoric strain and excess pore water pressure with the number of load cycles reached acceptable consistencies with the experimental results. Moreover, the effects of confining and deviatoric stresses were investigated. Not only rational developments of excess pore water pressure and plastic deviatoric strain but also nearly identical results under the same cyclic stress ratio (CSR) were obtained, which adequately confirmed the feasibility and reliability of the proposed model. Although this model was developed based on isotropically consolidated soils and contained varied parameters for different CSRs, it provides a framework contributing to rigorous model development for high-cycle conditions.